2000
DOI: 10.1053/rmed.1999.0699
|View full text |Cite
|
Sign up to set email alerts
|

Home mechanical ventilation in Sweden, with reference to Danish experiences

Abstract: The Swedish Society of Chest Medicine has started a national register of patients on home mechanical ventilation, to establish reliable national prevalence data and to accurately document patient and treatment characteristics to enable a scientific evaluation of this treatment. In this first collection of retrospective register data, covering patients on home mechanical ventilation at the register start on 1 January 1996, we found 541 patients, corresponding to 6.1/100000 inhabitants, using home mechanical ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 3 publications
1
28
0
2
Order By: Relevance
“…The French Register showed a 10-fold increase from 180 subjects in 1988 to 1,800 subjects in 1998. 13 Analysis of data from the Swedish National Register 21 and Swiss Regional Register 14 indicated a similar net annual increase of ϳ10%. A similar 10-fold increase was noted in the northern Netherlands but over a longer time period (1980 -2004).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The French Register showed a 10-fold increase from 180 subjects in 1988 to 1,800 subjects in 1998. 13 Analysis of data from the Swedish National Register 21 and Swiss Regional Register 14 indicated a similar net annual increase of ϳ10%. A similar 10-fold increase was noted in the northern Netherlands but over a longer time period (1980 -2004).…”
Section: Discussionmentioning
confidence: 92%
“…In the latter, subjects treated with invasive ventilation are a diminishing minority. According to data gathered in early 1990s in a single-center register in California, tracheostomized subjects accounted for 76% of HMV cases, 25 whereas the Swedish National Register documented 25% of tracheostomized cases before 1996 21 and only 6% in the following 10 y. 26 A pan-European survey (Eurovent) presenting data from 2001 to 2002 revealed only 13% of tracheostomized subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion in its use in the last 15 yrs was stimulated by the introduction of noninvasive ventilation via a mask and the recognition that more patient groups could benefit. Previous surveys of HMV have highlighted the experience of France [3], Italy [4], and Scandinavia [5]. A pan-European survey published in 1992, however, found that the collection of information about HMV was incomplete and erratic in many countries and it was not possible to detail many aspects of its use due to the lack of documentation [6].…”
mentioning
confidence: 99%
“…The Eurovent Survey found that HMV variability concerned both the number of prescriptions and the profile of patients for whom this treatment was prescribed, neither of which was related to the characteristics of the healthcare system or the economic situation in the country involved [1]. The national Swedish HMV register also highlighted variability in prescription within the country itself, despite a similar level of healthcare coverage [14,15]. In Denmark, there are only 2 centers that prepime pime pime pime p pi im me e EDITRICE …”
Section: Discussionmentioning
confidence: 99%
“…A strength of this study is the type of analysis performed, based on available administrative data, which provides a good complement to scribe HMV; in this country, the prevalence of HMV is low, and the therapy is usually indicated in younger patients with neuromuscular diseases [14]. A recent study on the variability of HMV in Australia and New Zealand suggested that, in addition to variability in prevalence, HMV was more likely to be started in obese patients in New Zealand than in Australia [16].…”
Section: Original Articlementioning
confidence: 99%